Feasibility and acceptability of mobile phone platforms to deliver interventions to address gender-based violence among Syrian adolescent girls and young women in Izmir, Turkey. Issue 2 (2nd April 2020) - Yankah, Ekua; Mohamed, Omar; Wringe, Alison; Afaneh, Osama; Saleh, Mohamad; Speed, Olivia; Hémono, Rebecca; Relyea, Bridget; Ibrahim, Mahad; Sandhu, Jaspal; Scott, Jennifer
ABSTRACT: Addressing gender-based violence risks among displaced adolescent girls and young women (AGYW) is challenging. Delivering interventions through mobile phone platforms could help overcome challenges and tailor services, but formative research to inform their development is lacking. We explored the feasibility and acceptability of mobile phone platforms to deliver interventions such as targeted public safety and information alerts to address gender-based violence (GBV) among Syrian AGYW in Izmir, Turkey. We conducted a qualitative study in August 2016 with 29 Syrian refugees aged 15 years and older through seven focus group discussions (three with young women, two with young men, and two with adults of mixed gender). Topics covered mobile phone usage and the perceived benefits and challenges of mobile phones for delivering interventions to address GBV. Discussions were led by trained facilitators, audio-recorded, transcribed and translated into English. Transcripts were coded and analyzed thematically. We found that access to mobile phones among AGYW was widespread and there were gendered expectations that influenced phone use. Key concerns among AGYW included perceived personal data security risks and data privacy as phones were commonly shared with family members. Most adults were supportive of targeted public safety and information alerts to promote safety among AGYW, but wanted to be consulted about content development. Piloting a short message service (SMS)-based intervention was challenging due to national-level restrictions on accessing mass SMS delivery mechanisms in a context of political unrest. In conclusion, mobile phones would provide a feasible platform to deliver GBV prevention interventions, such as public safety & information alerts, to AGYW if strategies to protect users' privacy and minimize security risks are in place, and the community is involved in designing content. Their feasibility depends on access to mobile networks, which may be restricted in some settings.